New Gnamptodontinae (Hymenoptera: Braconidae) from China and Vietnam, with two genera new for China and seven new species - Tian, Xiao-Xia; van Achterberg, Cornelis; Wu, Jia-Xuan; Tan, Jiang-Li (Zootaxa, 2020)
The genus Pseudognaptodon Fischer, 1965 (Hymenoptera, Braconidae, Gnamptodontinae) is reported for the first time from the Palaearctic region, Neognamptodon Belokobylskij, 1999 is new for the Oriental region and both genera are new for China. Seven new species are described and fully illustrated: Pseudognaptodon sinensis Tan & van Achterberg, sp. n. from China (Shaanxi), P. curvinervis van Achterberg, sp. n., P. bidoupensis van Achterberg, sp. n., P. longi van Achterberg, sp. n. from Vietnam, Neognamptodon laticauda Tan & van Achterberg, sp. n. from China (Yunnan), Tamdaona brevizona van Achterberg, sp. n. and T. sculpturata van Achterberg, sp. n. from Vietnam. A key to the tribes and genera of the Gnamptodontinae are given, together with keys to species of Pseudognaptodon (Old World), Neognamptodon, and Tamdaona Belokobylskij, 1994. The phylogeny and distribution of the Gnamptodontinae is discussed, Tamdaona Belokobylskij, is transferred from the Exothecinae to the Gnamptodontinae, and included in a new tribe, Tamdaonini van Achterberg, trib. n., together with Neognamptodon Belokobylskij. Gnamptodon novobritannicus Fischer, 1971, from Bismarck Archipelago is transferred to the latter genus (Neognamptodon novobritannicus (Fischer, 1971) comb. n.). Pseudognaptodon striatus Williams, 2004 (not P. striatus Braga & Penteado-Dias, 2002), is renamed P. williamsi van Achterberg, nom. n., and P. carinatus Williams, 2004 (not P. carinatus Cirelli & Penteado-Dias, 2002) is renamed P. carinatoides van Achterberg, nom. n. Tobiasnusa Papp, 2004, is a new synonym of Alysdacnusa Tobias & Perepetchayenko, 1995 (syn. n.) and Alysdacnusa atomus (Papp, 2004) is a new combination (comb. n.).